A Modified PSO Algorithm Based on Cache Replacement Algorithm - Mingyue Feng; Hua Pan (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
Recently, the research of the PSO algorithm has gained more attention. The performance of the PSO algorithm can be improved by using hybrid techniques. In this paper, to solve the problem of slow convergence and optimize the PSO algorithm performance, we propose a new algorithm - Cache Replacement Search PSO (CRS-PSO), which integrates basic PSO and the idea of cache design in the computer realm. The experimental results show that the proposed CRS-PSO can effectively solve the slow convergence problem and give a better performance than PSO alone.